OPTIMIZATION OF POTATO FLOUR FOR DEVELOPMENT OF BISCUITS BY USING RESPONSE SURFACE METHODOLOGY - Giri, Namrata Ankush; Mridula, D (Potato Journal, 2017)
The present study was concerned with to optimize the formulation of potato flour for development of biscuits using a central composite design of Response Surface Methodology. The variables considered for the study were potato flour (20-50%) and refined wheat flour (50-80%) while the responses were spread ratio, sensory texture and overall acceptability. Potato flour and refined wheat flour both significantly affected (p<0.05) spread ratio of biscuits whereas sensory texture and overall acceptability was significantly affected by only potato flour. The optimization was carried out in order to know which of the combination of potato flour and wheat flour will give the best texture and overall acceptability to biscuits. The sample containing 20% potato flour and 50% refined wheat flour was found most acceptable by sensory panelists and therefore optimized.